2006
DOI: 10.1097/01.ijg.0000212214.18018.41
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Rate of Nonresponders to Latanoprost Therapy

Abstract: This multicenter prospective study found only 14 of 340 nonresponders to latanoprost. In the cross-over trial on nonresponders, IOP reduction reached statistical significance only after brimonidine, but their small number reduced its statistical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…In similar populations, the Travoprost Study Group 12 and the Bimatoprost/Latanoprost 29 Study Group found 13.5% and 51.5% of patients, respectively, to be nonresponders to latanoprost. In the current study, we used the same criteria as the LSG to define a nonresponder; we faced difficulties finding this type of patient because of the low percentage, with only 19 subjects among the large population of glaucomatous patients visiting the 5 referral centers involved in this study, which agrees with the data reported by Rossetti et al 11 However, our final sample size was similar to that of the other studies. Another limitation is the relatively short follow-up period for assessment of latanoprost response, because there may be late nonresponders and late responders, as described by the LSG.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In similar populations, the Travoprost Study Group 12 and the Bimatoprost/Latanoprost 29 Study Group found 13.5% and 51.5% of patients, respectively, to be nonresponders to latanoprost. In the current study, we used the same criteria as the LSG to define a nonresponder; we faced difficulties finding this type of patient because of the low percentage, with only 19 subjects among the large population of glaucomatous patients visiting the 5 referral centers involved in this study, which agrees with the data reported by Rossetti et al 11 However, our final sample size was similar to that of the other studies. Another limitation is the relatively short follow-up period for assessment of latanoprost response, because there may be late nonresponders and late responders, as described by the LSG.…”
Section: Discussionsupporting
confidence: 92%
“…10 The rates of response to latanoprost vary among populations, from 4.1% in an Italian population 11 to 13.5% in American populations. 12 In this study, we evaluated possible associations between the SNPs of the genes coding for MMP-1, -2, -3, -9, and -17 and the PTGFR gene in a white Spanish population of glaucomatous patients treated with latanoprost monotherapy.…”
mentioning
confidence: 99%
“…It has been reported that the IOP-lowering effect may differ among different PGs; the presence of both responders and nonresponders to the same type of drug has been reported. Camras and Hedman17 and Rossetti et al18 reported that 4.1% of subjects were nonresponders, which were defined as patients who did not experience a decrease in IOP of at least 15% from the baseline IOP. However, no studies have examined the response of one PG nonresponder to other PGs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the effectiveness of PGs in lowering IOP in patients with NTG 414. However, it has been reported that the IOP-lowering effect may differ among different PGs, and the presence of responders and nonresponders to the same type of drug has been reported 1518. Thus, many questions remain regarding the effects of PGs in the management of NTG.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent meta-analyses of clinical trials showed that the IOP-lowering efficacy was similar among different PGAs [1][2][3], individual evaluation of IOP reduction shows variability among patients, and nonresponders who respond poorly to PGAs are common [4,5]. For the non-responders, switching within the medication class of PGAs is reported to be effective [6,7].…”
Section: Introductionmentioning
confidence: 96%